2014
DOI: 10.1590/s1679-87592014079706204
|View full text |Cite
|
Sign up to set email alerts
|

POPULATION BIOLOGY OF SEABOB-SHRIMP Xiphopenaeus kroyeri (Heller, 1862) CAPTURED ON THE SOUTH COAST OF PERNAMBUCO STATE, NORTHEASTERN BRAZIL

Abstract: A B S T R A C TThis paper aims to describe the population dynamics and to evaluate the stock of the seabob-shrimp Xiphopenaeus kroyeri on the coast of Pernambuco. Sampling was carried out between August/2011 and July/2012 in Sirinhaém, southern coast of Pernambuco. A total of 1201 individuals were analyzed, 673 females and 528 males. Total length (Lt) of females varied from 4.5 to 13.5 cm while the Lt of males ranged between 4.0 and 11.0 cm. The relationship between the Lt and carapace length and Lt and total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 19 publications
0
19
0
3
Order By: Relevance
“…The target species (Penaeus subtilis, Xiphopenaeus kroyeri, and P. schmitti) caught by trawlers in the south coast of Pernambuco, are either close or at maximum exploitation rates (Lopes et al, 2014;Silva, 2015b). This fishery is hence increasingly vulnerable in the future due to the lack of adequate regulatory legislation in the study area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The target species (Penaeus subtilis, Xiphopenaeus kroyeri, and P. schmitti) caught by trawlers in the south coast of Pernambuco, are either close or at maximum exploitation rates (Lopes et al, 2014;Silva, 2015b). This fishery is hence increasingly vulnerable in the future due to the lack of adequate regulatory legislation in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…In northeast Brazil, approximately 100,000 people depend directly or indirectly on the fishery of these crustaceans for their living (Santos et al, 2006). However, no effective measures for the regulation of shrimp trawling are available now in Pernambuco, in contrast with other Brazilian states, where there is regulatory legislation (Lopes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The CCRF recommends that the entire catch should be managed in an ecologically sustainable manner; thus, a regulation for this area should be established considering the main species involved (target and bycatch). Previous studies in the region have shown that the bulk of the catch of the shrimp fishery in Pernambuco shares the same feeding ground and season of reproduction (e.g., between October and March) (Lopes et al 2014, 2017, 2018, Silva Júnior et al 2015, Eduardo et al 2018b) and a closed season could be established during the austral summer. In addition, the application of BRD (e.g., fisheye, grid and square mesh) used to exclude fish and other small bycatch from the trawl (Broadhurst 2000, Eayrs 2007, Larsen et al 2017) might be a good conservation tool.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the region have shown that most of the catch (bycatch and target) of the shrimp fishery in Pernambuco occurs in the same area and share the same reproduction season, i.e. between October and March (Lopes et al, 2014(Lopes et al, , 2017Silva et al, 2015aSilva et al, ,b, 2016. Hence, the establishment of Marine Protect Areas (MPA) or a fishery-closing period should improve the conservation of the species and marine habitats exploited by this fishery in Pernambuco.…”
Section: Discussionmentioning
confidence: 99%